2022
DOI: 10.3390/ani12111349
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Thoracolumbar Variations and NR6A1 Gene Polymorphisms Potentially Associated with Body Size and Carcass Traits of Dezhou Donkey

Abstract: The number of thoracolumbar vertebrae is a quantitative trait positively correlated with the economic traits of livestock. More thoracolumbar vertebrae individuals could genetically be used to improve the livestock population, as more thoracolumbar vertebrae means a longer carcass, which could bring more meat production. Nuclear receptor subfamily 6 group A member 1 (NR6A1) is considered a strong candidate gene for effecting the number of vertebrae in livestock. The purposes of this study are as follows: (a) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The g.15179224C>T and g.15179674G>A sites may alter the binding of shear factor binding proteins to target sequences, leading to the appearance of phenotypic variants. Furthermore, the association of the HOXC8 gene with CW in Dezhou donkeys might be related to adipose differentiation and lipid deposition during livestock development and the regulation of LL and LN by the HOXC8 gene [ 18 , 44 , 45 ]. The correlation of the HOXC8 gene with LL and LN was possibly attributed to the differential expression of the HOXC8 gene during skeletal differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The g.15179224C>T and g.15179674G>A sites may alter the binding of shear factor binding proteins to target sequences, leading to the appearance of phenotypic variants. Furthermore, the association of the HOXC8 gene with CW in Dezhou donkeys might be related to adipose differentiation and lipid deposition during livestock development and the regulation of LL and LN by the HOXC8 gene [ 18 , 44 , 45 ]. The correlation of the HOXC8 gene with LL and LN was possibly attributed to the differential expression of the HOXC8 gene during skeletal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous studies, it has been confirmed that gene single nucleotide polymorphisms do cause changes in body size, vertebrae number, and production performance in Dezhou donkeys. For example, the nuclear receptor subfamily 6 group A member 1 ( NR6A1 ) g.18114954C>T can significantly increase the number of lumbar vertebrae, the total number of thoracolumbar vertebrae, and carcass weight in Dezhou donkeys, which can be a candidate gene to explore the genetic mutation affecting vertebral development [ 18 ]. However, the research is not sufficient and more genes need to be examined to screen for more molecular markers to accelerate the selection process of new strains of Dezhou donkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Hide weight was weighted immediately after slaughter. Blood samples were collected from the jugular vein using EDTA blood collection tubes and immediately stored in a −20 °C refrigerator [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 396 genomic DNA samples of Dezhou donkeys were extracted from whole blood with the M5 FlexGen Blood DNA kit (TIANGEN, Beijing, China) [ 17 ]. Then, DNA purity (OD 260 /OD 280 ) was detected using a spectrophotometer (B500, Metash, Shanghai, China) and the quantity of extracted genomic DNA was detected by 1% agarose gel [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation